Effects of the apolipoprotein E polymorphism on uptake and transfer of cell-derived cholesterol in plasma. - Huang, Y (1995)
The reverse cholesterol transport is initiated by the uptake of cholesterol into minor subfractions of high density lipoproteins (HDL) which contain either apolipoprotein (apo) A-I or apoE as their only apolipoproteins. From these initial acceptors, which are termed prebeta1-LpA-I and gamma-LpE, respectively, cell-derived cholesterol is transferred to LDL via the bulk of HDL termed alpha-LpA-I. In this study we analyzed the effect in plasma of the genetically determined apoE polymorphism on the formation of gamma-LpE, uptake and transfer of cell-derived cholesterol to LDL. Gamma-LpE was immunologically detectable in plasmas of individuals carrying at least one apoE3-allele but not in apoE3-free plasmas. During one minute incubation with [3H]cholesterol-labeled fibroblasts, gamma-LpE of plasmas from apoE3/3 subjects accumulated 7 and 13-fold more radioactivity than the respective fractions in plasmas from apoE2/2- and apoE4/4-subjects, respectively. Totally, 30% less [3H]cholesterol was released into plasmas of apoE2/2 and apoE4/4-individuals as compared with plasmas of apoE3/3-subjects. Moreover, plasmas of apoE3/3 individuals accumulated 50% and 65% more cell-derived [3H]cholesterol in alpha-LpA-I2 than plasmas of apoE4/4 and apoE2/2-subjects, respectively. These results indicate that the apoE-polymorphism is an important determinant of the uptake and transfer of cell-derived cholesterol in plasma.